1984
DOI: 10.1128/aac.26.6.837
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the in vitro activity of amphotericin B against Aspergillus spp. by tetracycline analogs

Abstract: Strains of Aspergillus fumigatus, Aspergillus flavus, and Aspergillus niger were tested for in vitro susceptibility to amphotericin B alone and in combination with fixed concentrations of tetracycline, doxycycline, or minocycline, using buffered minimal essential medium in microtiter plates. Enhanced inhibitory activity was seen, especially with combinations of amphotericin B and minocycline. Synergistic activity between amphotericin B and minocycline was observed in each of five isolates of each species when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…(6,16,17,26). As with PN, the above-mentioned antibacterial drugs inhibit the protein synthesis, and this could be an explanation of their positive interaction.…”
mentioning
confidence: 99%
“…(6,16,17,26). As with PN, the above-mentioned antibacterial drugs inhibit the protein synthesis, and this could be an explanation of their positive interaction.…”
mentioning
confidence: 99%
“…Since then, several studies demonstrated the in vitro synergisms between amphotericin B or fluconazole with azithromycin, clarithromycin, doxycycline, minocycline, or tetracycline against Aspergillus spp., Candida spp., and Fusarium spp. (18)(19)(20)(21)(22)(23), as well as other combinations of antibacterial and antifungal agents against pathogenic fungi, as reviewed by Afeltra and Verweij (24) and Liu et al (25).…”
mentioning
confidence: 99%
“…Various combinations of amph B and tetracycline anti biotics (tetracycline, doxicycline, minocycline) have been studied for activity against A. fumigants [102]. Synergistic activity of amph B and minocycline was observed in each of 5 isolates: time-kill curves showed eradication of A .…”
Section: Combinations O F Amphotericin B With Other Drugsmentioning
confidence: 99%
“…Synergistic activity of amph B and minocycline was observed in each of 5 isolates: time-kill curves showed eradication of A . fu migants at concentrations of amph B that were 4-to 8-fold lower in the presence of 5 or 15 gg/ml o f minocycline than with amph B alone [102].…”
Section: Combinations O F Amphotericin B With Other Drugsmentioning
confidence: 99%